Identifikasi Karakter Morfologi dan Respons Dua Kultivar Ubijalar (Ipomoea batatas L.) Lokal Kalimantan Timur Terhadap Pemupukan Fosfat - Santi, Santi; Setyawan, Setyawan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Identification of morphological characters and responses of two sweet potato cultivars (Ipomoea batatas L.) Kal-Tim local for Phosphate fertilization aims to identify morphological characteristics and find out the response and obtain the optimal dose of Phosphate fertilizer that provides the highest yield of fresh tubers to two local Kal-Tim sweet potato cultivars. Morphological character identification was carried out based on Descriptores for Sweetpotato. Meanwhile, the response of two local sweet potato cultivars to phosphate fertilization used a two-factor Factorial Design arranged in RAK with 5 replicates. The first factor of the cultivar (K) is: k1 = purple sweet potato and k2 = orange sweet potato. The second factor is Phosphate fertilizer (P), namely: p0 = 0 kg P2O5 ha-1; p1 = 16 kg P2O5 ha-1; p2 = 32 kg P2O5 ha-1; p3 = 48 kg P2O5 ha-1; p4 = 64 kg P2O5 ha-1. The results of morphological character identification showed that the length of the stem segments, the number of petals, the color of the petiole and leaf bones, the color of the young leaves, the flowering ability, the position of the pistil head, the color of the flesh and skin of the tubers, the shape and formation of the tubers showed the diversity between the two tuberous cultivars. The real interaction between sweet potato cultivars x Phosphate fertilizer was only found in the total sugar content. Cultivar treatment has a noticeable effect on the length and diameter of the stems, the number of bulbs per plant and the dry matter of the tubers. The heaviest fresh tuber yield was produced by the Purple sweet potato cultivar, which was 22.07 Mg ha-1. Meanwhile, the treatment of Phosphate fertilizer had a real effect on the length and diameter of the stem, the number and weight of tubers per plant, the weight of tubers per plot and the yield of fresh tubers per hectare. The yield of fresh tubers per the heaviest plot was produced by the treatment of Phosphate fertilizer 48 kg P2O5 ha-1, which is 23.67 Mg ha-1. The relationship between fresh tuber yield per hectare and phosphate fertilizer forms a quadratic regression, with the equation Y = 18.235 + 0.1585x - 0.0017x2 (R2 = 0.6151). Based on this equation, the optimum dose of Phosphate fertilizer was obtained of 46.62 kg of P2O5 ha-1 with a maximum yield of fresh tubers per hectare of 21.92 Mg ha-1. Meanwhile, the relationship between fresh tuber yield per hectare of each sweet potato cultivar and phosphate fertilizer was obtained as follows: YUngu = -0.0054x2 + 0.37775x + 18.328 (R2 = 0.8526) and Y orange = -0.0013x2 + 0.1539x + 17.627 (R2 = 0.9865). Based on this equation, the optimum dose of Phosphate fertilizer for Purple sweet potato and Orange sweet potato cultivars was obtained respectively, namely 34.95 kg P2O5 ha-1 and 59.19 kg P2O5 ha-1 with a maximum fresh bulb yield of 24.92 Mg ha-1 and 22.18 Mg ha-1 respectively.